(untitled) (Hoboken, N.J., 2007)
This book is the first book on this technique; it describes the theory of DPSM in detail and covers its applications in ultrasonic, magnetic, electrostatic and electromagnetic problems in engineering. For the convenience of the users, the detailed theory of DPSM and its applications in different engineering fields are published here in one book making it easy to acquire a unified knowledge on DPSM.
Keywords: Electromagnetic device,Engineering mathematics,Ultrasonic waves,Thiết bị điện từ,Toán công nghệ,Sóng siêu âm; Design and construction,Mathematics,Mathematical models,Thiết kế và xây dựng,Toán học,Mô hình toán